Fresno County Women Lawyers Dinner with Patricia Shiu and Nancy DeStefanis - Watkins, Howard::::::::: (1987)
California Women Lawyers President Patricia Shiu, Tracy Agrall, 1986 Fresno County Women Lawyers President Doris Coleman, Ruth Ratzlaff, 1987 Fresno County Women Lawyers President Karen Kern, Nancy DeStefanis, and Sandra Snyder